2015
DOI: 10.1016/j.atmosenv.2015.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Global impacts of surface ozone changes on crop yields and land use

Abstract: h i g h l i g h t sWe estimate ozone impacts on crop yields using high and low air pollution scenarios. Substantial crop losses can be avoided by air pollution control, especially in Asia. Climate policies can have co-benefits for crops due to reduced co-emissions. Reduced ozone damage will also reduce land use and associated carbon emissions. a b s t r a c tExposure to surface ozone has detrimental impacts on vegetation and crop yields. In this study, we estimate ozone impacts on crop production and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 38 publications
0
47
1
Order By: Relevance
“…At the coarsest resolution, the distribution of areas identified in TOAR-Vegetation as having vegetation at low or high risk of damage from ozone largely matches that predicted by global modelling of M12, AOT40 or W126 (Avnery et al, 2011;Chuwah et al, 2015;Fuhrer et al, 2016;Hollaway et al, 2012;Van Dingenen et al, 2009;). However, the high values for ozone metrics in TOAR-Vegetation at SEA sites tend to be underestimated in modelling studies.…”
Section: Comparison With Modelled Distributions Of Ozonementioning
confidence: 63%
See 1 more Smart Citation
“…At the coarsest resolution, the distribution of areas identified in TOAR-Vegetation as having vegetation at low or high risk of damage from ozone largely matches that predicted by global modelling of M12, AOT40 or W126 (Avnery et al, 2011;Chuwah et al, 2015;Fuhrer et al, 2016;Hollaway et al, 2012;Van Dingenen et al, 2009;). However, the high values for ozone metrics in TOAR-Vegetation at SEA sites tend to be underestimated in modelling studies.…”
Section: Comparison With Modelled Distributions Of Ozonementioning
confidence: 63%
“…However, the high values for ozone metrics in TOAR-Vegetation at SEA sites tend to be underestimated in modelling studies. It is more difficult though to align measurements included in TOARVegetation with modelled data due to uncertainties introduced by comparing site-specific data with grid square values presented at resolutions of 2.8° × 2.8° (Avnery et al, 2011;Hollaway et al, 2012) or 3° × 2° (Chuwah et al, 2015). Differences in the years used also confound detailed comparisons as the global modelling studies tend to have used earlier years such as 2000 (Avnery et al, 2011;Fuhrer et al, 2016;Hollaway et al, 2012) or 2005(Chuwah et al, 2015 whilst TOAR-Vegetation provides 5-year means for the period 2010-2014.…”
Section: Comparison With Modelled Distributions Of Ozonementioning
confidence: 99%
“…Although the figures are not very high (0.32 and 1.47%, respectively), it is important to realize that they could entail some indirect damage. For instance, CO is a precursor for the formation of tropospheric ozone (O3), which has been proven to have impacts on health [25,26] and agricultural systems [27]. Moreover, OC emissions are also a key element for the deposition of PM2.5 in the atmosphere.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Studies over the past several decades indicated that chronic O 3 exposure significantly decreased the production of forests (Proietti et al, 2016), crops (Avnery et al, 2011;Ghude et al, 2014;Chuwah et al, 2015) and grasslands (Gilliland et al, 2016). However, there are some exceptions where O 3 exposure promoted biomass accumulation under particular environmental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%